2018
DOI: 10.1167/iovs.17-23167
|View full text |Cite
|
Sign up to set email alerts
|

Symbol Discrimination Speed in Children With Visual Impairments

Abstract: Citation: Barsingerhorn AD, Boonstra FN, Goossens J. Symbol discrimination speed in children with visual impairments. Invest Ophthalmol Vis Sci. 2018;59:3963-3972. https://doi.org/ 10.1167/iovs.17-23167 PURPOSE. We measured visual acuity and visual discrimination speed simultaneously in children with visual impairments to determine whether they are slower than children with normal vision.METHODS. Five-to twelve-year-old children with visual impairments due to ocular dysfunction (VI o ; n ¼ 30) or cerebral vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…It did, however, cause response times to be significantly slower (by over 200%, in the bilateral-symmetric case), and compelled participants to make substantially more head-and eye-movements. These findings echo a recent report by Barsingerhorn and colleagues 64 , who observed that children with ocular dysfunction were slower at performing a simple spatial judgment (landolt-C orientation-identification) than their normal-sighted peers, even after the stimuli were matched in size for relative acuity. Taken together, such findings suggest that when characterizing vision loss, it may be prudent to move beyond simple functional measures of accuracy.…”
Section: Implications and Future Worksupporting
confidence: 90%
“…It did, however, cause response times to be significantly slower (by over 200%, in the bilateral-symmetric case), and compelled participants to make substantially more head-and eye-movements. These findings echo a recent report by Barsingerhorn and colleagues 64 , who observed that children with ocular dysfunction were slower at performing a simple spatial judgment (landolt-C orientation-identification) than their normal-sighted peers, even after the stimuli were matched in size for relative acuity. Taken together, such findings suggest that when characterizing vision loss, it may be prudent to move beyond simple functional measures of accuracy.…”
Section: Implications and Future Worksupporting
confidence: 90%
“…The results revealed that 40% of the children with visual impairments needed more time to discern optotypes (Barsingerhorn et al. 2018b) than one might expect from their reduced visual acuity alone.…”
Section: Discussionmentioning
confidence: 99%
“…), and they need more time for the discrimination of optotypes (Barsingerhorn et al. 2018b) compared to children with normal vision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations